Revamping field practicum: insights for future health services management professionals - Fatemeh Mohabati; Marzieh Arefi; Seyed Pouria Hedayati (BMC Medical Education)
Abstract Background The effectiveness of Health Services Management curricula relies heavily on practical experiences that reflect the evolving needs of the healthcare sector. This study focuses on revising Field Practicum 4 for undergraduate students to better prepare them for leadership roles in healthcare. Methods This qualitative and cross-sectional case study was conducted during the 2022–2023 academic year at Zabol University of Medical Sciences. Data were collected through semi-structured, in-depth interviews and document analysis of the undergraduate curriculum. Purposeful sampling was used to select a diverse group of interviewees, including faculty members, healthcare managers, graduates, and current students, with a total of 38 interviews conducted until data saturation was reached. Thematic analysis was performed using MAXQDA software version 11. The CIPP (Context, Input, Process, Product) evaluation model was applied to systematically assess and enhance the practicum program.For the quantitative data analysis, SPSS version 23 was utilized. Results The central finding from this study was the enhancement of productivity in Field Practicum 4. Thirteen core issues were identified and categorized into primary codes, including causal, contextual, intervening, focal, strategies, and outcomes. To achieve desirable outcomes through a fundamental revision strategy, it was decided that, in addition to students’ presence in hospitals (including the office of senior hospital managers and the quality improvement and accreditation unit), students should also be present in the deputyships and central units of Zabol University of Medical Sciences (treatment, resource development and management, food and drug administration, and the center for management of medical emergencies). Furthermore, students should engage with the county health insurance organization and a private insurance company to gain comprehensive familiarity with their operations. The level of consensus among the faculty members of the Health Services Management Department was at least 90%. The findings indicate that both students and internship supervisors generally rated the program positively (Mean > 4.5), although areas for improvement are highlighted, particularly in aspects of process and product. Conclusions The study concludes that revising Field Practicum 4 using the CIPP model provides a structured approach to enhancing practical training for Health Services Management students. Implementing these modifications in the apprenticeship syllabus is expected to improve the capabilities of graduates, better preparing them to meet the needs of healthcare system.